2012
DOI: 10.3310/hta16110
|View full text |Cite
|
Sign up to set email alerts
|

Management of frozen shoulder: a systematic review and cost-effectiveness analysis.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
203
2
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(236 citation statements)
references
References 252 publications
7
203
2
17
Order By: Relevance
“…Unfortunately, the same methodological shortcomings in case definition that have hampered interpretation of the risk factor literature apply equally to the studies of interventions. Table 3 summarises the principal conservative treatments for shoulder disorders together with the results of systematic reviews summarising the strength of the evidence in support of their efficacy for the treatment of shoulder pain/disability [76][77][78][79][80][81][82][83][84][85][86].…”
Section: Management Of Shoulder Disordersmentioning
confidence: 99%
“…Unfortunately, the same methodological shortcomings in case definition that have hampered interpretation of the risk factor literature apply equally to the studies of interventions. Table 3 summarises the principal conservative treatments for shoulder disorders together with the results of systematic reviews summarising the strength of the evidence in support of their efficacy for the treatment of shoulder pain/disability [76][77][78][79][80][81][82][83][84][85][86].…”
Section: Management Of Shoulder Disordersmentioning
confidence: 99%
“…In 2009, Blanchard et al, (12) who compared the effectiveness of corticosteroid injections with physiotherapeutic interventions for adhesive capsulitis, found greater improvement in pain, ROM and shoulder disability in favour of corticosteroid injections in the short-term (six weeks) and, to a lesser extent, in the longer-term (up to one year). Maund et al, in 2010, (13) performed a systematic review and cost-effectiveness analysis on common interventions used in adhesive capsulitis and concluded that there may be short-term benefi ts from adding a single intraarticular steroid injection to home exercise for patients with primary frozen shoulder of less than six months' duration, but the evidence was limited.…”
Section: Introductionmentioning
confidence: 99%
“…(4,6) Previous systematic reviews on the use of corticosteroid in adhesive capsulitis mostly found evidence of its short-term effectiveness. (10)(11)(12)(13) In 2003, Buchbinder et al (10) performed a systematic review of randomised and pseudorandomised trials on the use of corticosteroid injections (including 12 randomised controlled trials [RCTs] on adhesive capsulitis) in patients with shoulder pain; the authors concluded that, although the treatment may be benefi cial, its effect may be small and not well maintained. In 2006, Shah and Lewis (11) found that multiple (up to three) corticosteroid injections for the treatment of adhesive capsulitis improved pain and ROM for 6-16 weeks from the fi rst injection.…”
Section: Introductionmentioning
confidence: 99%
“…17 This report provides full details of methodology, search strategy, economic analysis, decision model, and suggestions for future research. An analysis of the effectiveness and cost effectiveness of interventions from available primary research is also included in this report.…”
mentioning
confidence: 99%